2022
DOI: 10.1002/mame.202200423
|View full text |Cite
|
Sign up to set email alerts
|

Cyanate Ester Resin with High Heat‐Resistance and Degradable Diacetal Structure: Synthesis, Polymerization, and Properties

Abstract: Cyanate resins are high‐performance thermosetting resins with excellent mechanical, thermal, and dielectric properties. In this work, a novel cyanate ester monomer, 3,9‐bis‐(4‐cyanato‐phenyl)‐2,4,8,10‐tetraoxa‐spiro[5.5]undecane structure (DBCE), is prepared based on a diphenol (DB) with a degradable diacetal structure. The characterization of the chemical structures and polymerization behaviors of the samples are achieved by nuclear magnetic resonance spectroscopy, fourier transform infrared spectroscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…We also compare how H bonding of THF with water and with sorbitan esters affects the COC band of THF. With pure THF, we observe a dominant COC stretch peak at ≈1,070 cm −1 (Liu et al, 2022), and a significantly smaller peak at 1,027 cm −1 (Sionkowska and Płanecka, 2013) (Figure 1). As mentioned above, upon mixing with water, the peak at ≈1,070 cm −1 splits into three peaks, at ≈1,070 cm −1 , ≈1,050 cm −1 and ≈1,040 cm −1 .…”
Section: Tailmentioning
confidence: 88%
“…We also compare how H bonding of THF with water and with sorbitan esters affects the COC band of THF. With pure THF, we observe a dominant COC stretch peak at ≈1,070 cm −1 (Liu et al, 2022), and a significantly smaller peak at 1,027 cm −1 (Sionkowska and Płanecka, 2013) (Figure 1). As mentioned above, upon mixing with water, the peak at ≈1,070 cm −1 splits into three peaks, at ≈1,070 cm −1 , ≈1,050 cm −1 and ≈1,040 cm −1 .…”
Section: Tailmentioning
confidence: 88%
“…19,20,46 Moreover, Xia et al synthesized a novel degradable cyanate ester featuring a diacetal structure with a high T g of 294 °C. 17 In our previous work, Wang et al prepared two high heat-resistant and degradable polybenzoxazines with T g of around 300 °C due to the presence of the rigid diacetal structure. 47 These studies demonstrate the potential of the acetal structure in achieving both high thermal resistance and degradability in polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the increasing application of polymer materials, the environmental impact of their waste has also been growing, particularly for thermosetting polymers with high cross-linking density. Three-dimensional cross-linking structures provide excellent heat resistance, rigidity, and dimensional stability. However, they also present significant challenges in terms of degradation and recovery. Many researchers have attempted to make thermosetting resins degradable by incorporating unstable structures such as ester, acetal, sulfur bond, Schiff base, and others. , It is important to acknowledge that these unstable structures can also have some adverse effects on the performance of materials, especially in terms of heat resistance. It has been observed that a high cross-linking density leads to improved thermal stability of the cross-linking structure and enhanced heat resistance of the material. However, achieving degradability in materials often requires a relatively low cross-linking density and the inclusion of unstable cross-linking structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation